Controlling the magic size of white light-emitting CdSe quantum dots. Issue 21 (23rd May 2018) - Dai, Sheng; Su, Yu-Sheng; Chung, Shu-Ru; Wang, Kuan-Wen; Pan, Xiaoqing
Abstract : By employing a particular non-coordinating solvent and long carbon chain amine, white-light emitting CdSe quantum dots with magic sizes and enhanced quantum yield can be prepared. Abstract : White light-emitting quantum dots (QDs) have shown brilliant prospects as a white-light source in solid-state lighting devices, however their commercial application is limited by their low fluorescence quantum yield (QY). Here, we report a facile thermal pyrolyzed organometallic route to synthesize white-light emitting CdSe QDs with enhanced QY, by employing a particular non-coordinating solvent and long carbon chain amine. By clarifying the three distinct growing stages of CdSe nanocrystals, we are able to determine the critical growth parameters for high quality magic size QDs. According to the optical measurement and advanced characterization result, the as-synthesized magic-size QD samples show an enhanced QY (up to 64%) and an ultra-high stability with no degradation even after 120 days, while the fabricated WLED devices also exhibit desirable properties ( e.g., high QY and CRI, decent efficacy), demonstrating progress towards the desired efficiency of a commercially viable solid-state lighting device.